PENGARUH INTEROVERNMENTAL REVENUE, PENDAPATAN ASLI DAERAH (PAD) DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA TIMUR - Ryansyah Ilham Sasti; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2022)
The monetary performance of local governments is a measure of the success of nearby government in managing resources coming from their areas or important authorities. control independently and collaboratively gives extraordinary provider to the network. The motive of this look at turned into to decide the effect of intergovernmental sales, local seed sales (PAD) and capital expenses on the monetary performance of the regency/town authorities in East Java in 2017-2020. This study used an associative method with a quantitative method. The statistics used are secondary information with a time collection of 4 years. the public uses the Audit record (LHP) received from the perfect Audit frame. The sampling method used focused sampling and acquired 29 districts and nine cities in East Java. more than one linear regression evaluation become used inside the records analysis. whilst processing data, IBM Statistical package deal for the Social Sciences type 22 is used. The results of this look at provide an explanation for that intergovernmental revenues have a terrible impact at the economic performance of nearby government. The VARIABLE PAD has a vast high-quality impact on the economic overall performance of the local authorities, and the variable capital expenditure does no longer have an effect on the monetary overall performance of the regional government.Keyword: Intergovernmental Revenue, Regional Original Revenue and Capital Expenditure, Regional Government Financial Performance.